The Power of Law in a Transnational World - Franz von Benda-Beckmann, Keebet von Benda-Beckmann, and Anne Griffiths (Berghahn Books, 2009)
Law is a source for constituting and legitimating power. It defi nes and validates positions and relations of power of persons or organizations over other persons, organizations and resources. It lays down in general terms which exercises of power are permissible or prohibited. It can be actualized in social interaction when the exercise of power is rationalized and justifi ed with reference to law.1 Of course, other means for constituting and legitimating power and exercising social control coexist and compete with legal ones. These include moral and ethical standards as well as naked, unabashed power based on the command and exercise of physical force. Yet even autocrats exercising power on the basis of ‘might is right’ o􀄞 en feel the need to legitimate their position through reference to a higher and more noble source. The ‘legal certifi cation of power’ (F. von Benda-Beckmann 2005: 3) is therefore a resource much sought a􀄞 er in local, national and transnational arenas. Earlier discussions on the relationship between law and power and the function of law for preventive and reactive social control situated law primarily in a national context.2 Over the last decades law has become an important factor in transnational relationships and is far less exclusively tied to a particular national state than before. National law is o􀄞 en made in response to transnational developments urging homogenization and assimilation. At the same time, it has become increasingly clear that the degree to which transnational developments reach out to local levels and how they are dealt with locally varies greatly. Moreover, the idea of legal pluralism drawing a􀄴 ention to the possibility that there may be sources of law other than the nation state has become far more widely accepted than it was only a few decades ago. Besides state-internal constellations, ‘global’ legal pluralism is a subject of intensive debate.3 In an earlier publication, we have explored some of these transnational dimensions of ‘mobile law and mobile people’ (F. von Benda-Beckmann, K. von Benda-Beckmann and A. Griffi ths2005). The present volume explores some of the connections between law and power, taking account of these new confi gurations.